Differential Effects of the Cannabinoid Agonist WIN55,212-2 on Delay and Trace Eyeblink Conditioning - Steinmetz, Adam B. (2013)
Central cannabinoid-1 receptors (CB1R) play a role in the acquisition of delay eyeblink conditioning but not trace eyeblink conditioning in humans and animals. However, it is not clear why trace conditioning is immune to the effects of cannabinoid receptor compounds. The current study examined the effects of variants of delay and trace conditioning procedures to elucidate the factors that determine the effects of CB1R agonists on eyeblink conditioning. In Experiment 1 rats were administered the cannabinoid agonist WIN55,212-2 during delay, long delay, or trace conditioning. Rats were impaired during delay and long delay but not trace conditioning; the impairment was greater for long delay than delay conditioning. Trace conditioning was further examined in Experiment 2 by manipulating the trace interval and keeping constant the conditioned stimulus (CS) duration. It was found that when the trace interval was 300 ms or less WIN55,212-2 administration impaired the rate of learning. Experiment 3 tested whether the trace interval duration or the relative durations of the CS and trace interval were critical parameters influencing the effects of WIN55,212-2 on eyeblink conditioning. Rats were not impaired with a 100 ms CS, 200 ms trace paradigm but were impaired with a 1000 ms CS, 500 ms trace paradigm, indicating that the duration of the trace interval does not matter but the proportion of the interstimulus interval occupied by the CS relative to the trace period is critical. Taken together the results indicate that cannabinoid agonists affect cerebellar learning the CS is longer than the trace interval.